Lexemic-etymological remarks on the Latin graphemic opposition < condiciō > ~ < conditiō > (Atti del Sodalizio Glottologico Milanese, 2014)
From the graphical-etymological point of view we must prefere [kon’ditʃio:] to [kon’ditsio:] inside syntagms in current use such as par condiciō or condiciō sine quā nōn. The interference between the two lexemes is old and widely documented. Sources and etymological analysis convince us to hypothesize an exact starting point of the following lexematic development: ① (dicō) (*-deyk̑- / *-dik̑-) “con-declarated pact”, from which ② / ③ (with synonimical allotropy) ~ ④ (condō)(*-dhē(y)- / *-dhō(y)- / *-dhī- “co-foundation” / ⑤ (condiō) (*kwend(h)- / *kwond(h)-) “seasoning”, with homophony in ②③ and with homophony-homography in ④⑤. We can notice a double cruciality, on one hand into the quantity opposition on phonematic level, on the other, where this appears neutralizated, into the meaning opposition on semantematic level. KEYWORDS: etymology, Latin, script, homophones, homographs